Pengelolaan Program Tahfidz Al-Qur’an Dalam Membentuk Generasi Qur’ani Di SMP Negeri 1 Sampang - Badruttamam, Badruttamam; Aulidia, Sumrotul; Zainuddin, Zainuddin; Faddol, Moh (AL -ALLAM, 2023)
The Tahfidz Al-Qur'an Program in Forming a Qur'anic Generation at SMPN 1 Sampang. This research was conducted to find out how the Management of the Tahfidz Al-Qur'an Program conducted at SMPN 1 Sampang is running well, and to find out the supporting and inhibiting factors in managing the Tahfidz Al-Qur'an Program at SMPN 1 Sampang. The approach used is a descriptive qualitative approach, while this type of research is field research using observation, interview and documentation data collection techniques. The subjects in this study were school principals, Tahfidz teachers, BK teachers, guardians and students. The results showed that the Management of the Al-Qur'an Tahfidz Program at SMPN 1 Sampang in collaboration with the UMMI FOUNDATION was carried out by implementing four Management Functions namely: Planning, Organizing, Actuating and Controlling. In implementing the Tahfidz Al-Qur'an program at SMPN 1 Sampang, they received a lot of support, especially from the school principal. Apart from the principal, all teachers and parents of students also supported the Tahfidz program at SMPN 1 Sampang. The obstacles faced are located on the level of students' ability to read the Al-Qur'an, and the feeling of laziness in participating in the implementation of the Tahfidz Program. The results to be achieved from the existence of this Tahfidz Program are that students are able to read the Al- Qur'an and memorize according to predetermined targets and love the Al-Qur'an more.